Biostratigraphy of Yamama Formation at Luhais and Rifaee oilfields, Southern Iraq - Khazaal, Farah A.; Shakir, Luay S. (Iraqi Journal of Science, 2022)
Yamama Formation is the most important and widespread Lower Cretaceous Formation in Iraq. Yamama Formation in the Luhais well-12 and Rifaee well-1 are composed of dolomitized in some places and foraminifera and algae bearing limestone, 19 genera and species of foraminifera, 10 genera and species of algae. Two biozones were distinguished Pseudochrysalidina arabica Range zone and Pseudocyclammina lituus Range zone. The age of the formation was determined as Berriasian – Valanginian according to these biozones of Foraminifera. In this study, bryozoa, Gastropoda and Pelecypoda are recorded but less than Foraminifera.